Arterial remodeling in older patients with arterial hypertension - A. V. Agafonov; A. V. Tuev; L. A. Nekrutenko; Yu. V. Bochkova (Российский кардиологический журнал, 2005)
The aim of the study was to investigate remodeling and stiffness of elastic and muscle-type arterial walls in elderly arterial hypertension (ElAH) patients, in comparison with their relatively healthy peers. The study included 66 ElAH patients and 28 age- and gender-matched controls, with normal blood pressure (BP) levels. Ultrasound examination of brachial and common carotid arteries was performed; ultrasound vascular anatomy and stiffness parameters (pulse wave velocity, Yung and Peterson modules, circumference tension) were assessed. In ElAH, increased arterial stiffness, due to its active and passive components, was observed for both elastic and muscle-type arteries. In ElAH patients, carotid artery remodeling was more advanced than that for brachial artery. The most sensitive parameter of muscle-type artery remodeling was wall: lumen ratio.